Identification of Human S100A9 as a Novel Target for Treatment of Autoimmune Disease via Binding to Quinoline-3-Carboxamides - Björk, Per; Björk, Anders; Vogl, Thomas; Stenström, Martin; Liberg, David; Olsson, Anders; Roth, Johannes; Ivars, Fredrik; Leanderson, Tomas (PLOS Biology, 2009)
Despite more than 25 years of research, the molecular targets of quinoline-3-carboxamides have been elusive although these compounds are currently in Phase II and III development for treatment of autoimmune/inflammatory diseases in humans. Using photoaffinity cross-linking of a radioactively labelled quinoline-3-carboxamide compound, we could determine a direct association between human S100A9 and quinoline-3-carboxamides. This interaction was strictly dependent on both Zn++ and Ca++. We also show that S100A9 in the presence of Zn++ and Ca++ is an efficient ligand of receptor for advanced glycation end products (RAGE) and also an endogenous Toll ligand in that it shows a highly specific interaction with TLR4/MD2. Both these interactions are inhibited by quinoline-3-carboxamides. A clear structure-activity relationship (SAR) emerged with regard to the binding of quinoline-3-carboxamides to S100A9, as well as these compounds potency to inhibit interactions with RAGE or TLR4/MD2. The same SAR was observed when the compound's ability to inhibit acute experimental autoimmune encephalomyelitis in mice in vivo was analysed. Quinoline-3-carboxamides would also inhibit TNFα release in a S100A9-dependent model in vivo, as would antibodies raised against the quinoline-3-carboxamide–binding domain of S100A9. Thus, S100A9 appears to be a focal molecule in the control of autoimmune disease via its interactions with proinflammatory mediators. The specific binding of quinoline-3-carboxamides to S100A9 explains the immunomodulatory activity of this class of compounds and defines S100A9 as a novel target for treatment of human autoimmune diseases.